SOME ISSUES OF ENSURING THE STABILITY OF THE ELECTRIC POWER SYSTEM - Matevosyan, Hamlet; Gharibyan, Haykandukht (Crisis Management and Technologies, 2025)
This article considers the issues of ensuring the stability of the operation of the objects of the electric power system in emergency situations or in conditions of military operations, related to the issues of reducing the vulnerability of the system under consideration to external influences, as well as inherent, sociogenic hazards, preventing and preventing certain dangers. The fact that there are almost no information databases and statistical data on their impacts, losses, caused emergency situations, etc., is also substantiated, considering it as a complete system consisting of various subsystems, which can increase and ensure the stability of the operation of the aforementioned electric power system.